2020
DOI: 10.1097/md.0000000000022386
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator for the management of patients with severe pneumonia

Abstract: Background: This study will assess the efficacy and safety of ventilator for the management of severe pneumonia (SP). Methods: This study will search the following electronic databases in MEDLINE, EMBASE, Web of Science, PsycINFO, Cochrane Library, CNKI, and Scopus from the beginning to present without language restrictions. Two authors will screen all records according to the eligibility criteria; assess study quality; and extract all essential data from eligible studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The morbidity and mortality of pneumonia both rank first among children's diseases 15 . Without timely and effective diagnosis and treatment, pneumonia can easily develop into severe pneumonia accompanied with serious complications, such as RF, seriously threatening children's health and life safety 16 . LncRNA CASC2 is closely related to the occurrence and development of various human lung diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morbidity and mortality of pneumonia both rank first among children's diseases 15 . Without timely and effective diagnosis and treatment, pneumonia can easily develop into severe pneumonia accompanied with serious complications, such as RF, seriously threatening children's health and life safety 16 . LncRNA CASC2 is closely related to the occurrence and development of various human lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Without timely and effective diagnosis and treatment, pneumonia can easily develop into severe pneumonia accompanied with serious complications, such as RF, seriously threatening children's health and life safety. 16 LncRNA CASC2 is closely related to the occurrence and development of various human lung diseases. It has been reported that CASC2 can inhibit the progression of lung adenocarcinoma and is associated with drug resistance in cancer patients.…”
Section: Discussionmentioning
confidence: 99%